Improving Arabic Vocabulary Mastery through the Drops Application among Seventh-Grade Madrasah Tsanawiyah Students - Almujaddid, Abdurrahman; Zainal, Abdul Qahar; Syahid, Akhmad; Malla, Agussalim Beddu; Surani (Program Studi Pendidikan Bahasa Arab, Fakultas Agama Islam, Universitas Muslim Indonesia, 2025)
This study aims to examine the implementation of the Drops application–based learning media in Arabic language learning, particularly in vocabulary (mufradat) instruction, and to determine the extent to which the application improves students’ vocabulary mastery at the seventh grade of MTsN 2 Makassar. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The study was conducted in two cycles involving 36 students of class VII.5 at MTsN 2 Makassar. Data were collected through observation, tests (pre-test and post-test), and documentation. Data analysis was carried out using qualitative and quantitative approaches, specifically comparative descriptive statistics. The results indicate that the use of the Drops application as a learning medium creates an interactive, enjoyable, and motivating learning environment, encouraging students to participate more actively in the learning process. Improvement in vocabulary mastery was evident from the students’ learning outcomes, which showed significant increases in each cycle. The percentage of students achieving mastery increased from 5.56% in the pre-cycle to 52.78% in Cycle I and reached 86.11% in Cycle II. Therefore, the use of the Drops application–based learning media is proven to be effective in improving students’ Arabic vocabulary mastery